FIGURATIONS OF CELEBRITY EVERYDAY LIFE: REPRESENTATION, AUTHENTICITY, AND PROXIMITY ON SOCIAL MEDIA - Prado, Denise (AoIR Selected Papers of Internet Research, 2026)
This study examines the construction of celebrity everyday life on social media, focusing on how artists strategically intertwine their cultural productions with personal narratives to cultivate perceived intimacy and authenticity. Drawing upon the theoretical frameworks of face management and the everyday, this research analyzes the Instagram profile of Liniker, a prominent Black transgender artist in Brazil.Liniker’s profile serves as a platform for showcasing both her artistic endeavors and her daily life, challenging traditional representations of transgender women. Employing a dual analytical approach, combining panoramic observation and detailed visual analysis, the study explores how Liniker’s posts, categorized into promotional and everyday life themes, contribute to a complex performative construction of self. The analysis reveals that behind-the-scenes content emphasizes collaborative efforts and affective bonds, while musical partnerships highlight her integration into a prestigious cultural field. Individual images, including selfies and posed photographs, project intimacy towards her followers.By juxtaposing artistic achievements with quotidian experiences, Liniker broadens visual representations, challenging prevailing narratives that often depict transgender women in contexts of violence. Her portrayal of success, love, and happiness diversifies life potentials and contributes to the discourse on transgender rights. This platform facilitates the articulation of aspirational life possibilities, interweaving professional success, personal relationships, and the visible affirmation of transgender identity, thereby contributing to the study of celebrity culture, digital media, gender, and everyday life.